Interspecific differences and ecological correlations of ultraviolet radiation tolerance in low- and high-altitude fishes - Gu, Haoran; Li, Songtao; Wang, Haoyu; Zhu, Shudang; Yuan, Dengyue; Wang, Zhijian (Frontiers in Marine Science, 2022)
Ultraviolet radiation (UVR) is a ubiquitous environmental factor and with complex and diverse effects on organisms, and the UVR tolerance of species varies due to selection, adaptation and evolution. This study aimed to improve our understanding of the interspecific differences in UVR tolerance of fishes. First, we compared skin histology between high-altitude fishes and their low-altitude relatives. Second, we assessed the skin histological changes of 22 fish species after UVR exposure and quantified their damage levels. Finally, the factors affecting the difference in UVR tolerance among fishes were studied. Thin or absent scales was a common characteristic of high-altitude fishes in different taxonomic groups, but other skin structure parameters (the thickness of the dermis and epidermis, the size and number of mucous and club cells) did not show convergence. After UVR exposure, the size and number of mucous cells and club cells in the experimental fishes were generally reduced, but the changes in epidermal and dermal thickness varied among species. The change rata of melanin area was strong negatively correlated with the level of damage, indicating that increased melanin was helpful to reduce UVR damage. On the whole, the skin histological changes of high-altitude fishes after UVR exposure did not differ from those of low-altitude fishes. However, the epidermis and dermis of Gymnocypris eckloni and Oncorhynchus mykiss, which had the highest UVR tolerance, were nonpathologically thickened, indicating that they may contribute to UVR tolerance. There were significant interspecific differences in UVR tolerance among the experimental fishes, with high-altitude and cold water fishes showing stronger UVR tolerance. Interestingly, some low-altitude cold water fish (e.g., O. mykiss) also showed high UVR tolerance, suggesting that besides high-altitude adaptation, low-temperature adaptation also may play an important role in organismal adaptation to UVR.